The reality of Nursing Continuing Education in the Public Health Services. A descriptive study - Mônica Motta Lino; Vânia Marli Schubert Backes; Sandra Marcia Soares Schmidt; Fabiane Ferraz; Marta Lenise do Prado; Sabrina Telma Martins (Online Brazilian Journal of Nursing, 2007)
The present study has as an objective to discover how the proposal for the nursing continuing education are constituted in the public health services of Florianopolis/SC; to describe and analyze the conceptions that fundamental the development of these proposals in the services in the form of constructing a political institutional of Continuing Education and knowledge of the political Permanent Education of the Health Ministry. The analytic procedure of data collected, through the means of semi – structured interviews, were the content analysis, including pre – analysis; analytical description and interferential interpretation. The study group, were 10 nursing professionals responsible for the continuing education of the health institution studied. The results indicates that continuing nursing education in the public services of Florianopolis needs a better attention on the part of the representation of the Permanent Education Polo, such as focalize as a political strategy bettered systematized.